Molten Salt Synthesis of Photocatalyst Material SrBi4Ti4O15 for Methylene Blue Degradation - al-Abror, Muhammad Lathif; Hastuti, Erna; Prasetyo, Anton (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2022)
The four-layered Aurivillius SrBi4Ti4O15 compound has been reported to be potentially used as a photocatalyst material. In this research, SrBi4Ti4O15 was prepared by the molten salt method using NaCl/KCl and then used to degrade methylene blue. The analysis of sample diffractogram indicated that the SrBi4Ti4O15 was obtained but there was still the impurities of Bi4Ti3O12. The micrograph showed that particle shape of SrBi4Ti4O15 is plate-like (sheets) with a lot of agglomeration. The band gap energy of SrBi4Ti4O15 is 3.14 eV (394.85 nm), according to the Kubelka-Munk calculation from the spectrum of reflectance. The photocatalytic test results showed that SrBi4Ti4O15 degraded methylene blue to 47.8% in 120 minutes.